Conducting research with young people at the margins - lessons learnt and shared through case studies in Cambodia, India, Sweden and Zambia - Frida Jonsson; Puthy Pat; Chama Mulubwa; Bhoomikumar Jegannathan; Kaaren Mathias (BMC, 2022)
Abstract Building on the value of engaging with and enabling the participation of marginalised young people in research, the aim of this article was to profile practical and procedural issues faced when conducting studies with young people who experience some form of marginalisation. Drawing on observations and research experiences from four diverse case studies involving young people who were either imprisoned in Cambodia, living in informal urban communities in North India, residing in rural northern Sweden or attending school in rural Zambia, learnings were identified under three thematic areas. Firstly, a need exists to develop trusting relationships with stakeholders, and especially the participating young people, through multiple interactions. Secondly, the value of research methods that are creative and context sensitive are required to make the process equitable and meaningful for young people. Thirdly, it is important to flatten power relations between adults and young people, researchers and the researched, to maximise participation. These findings can inform future youth research in the field of global public health by detailing opportunities and challenges of engaging in research with young people on the margins to promote their participation.